Manga Studio Ex 5 cookbook : over 90 hands-on recipes to help you create digital comics, from page setup to exporting the final product /: over 90 hands-on recipes to help you create digital comics, from page setup to exporting the final product. (2015) - Staley, Elizabeth
No abstract available